IMPLEMENTASI KEBIJAKAN PEMBANGUNAN ZONA INTEGRITAS DALAM PERSPEKTIF GOVERNING UNTUK PENCEGAHAN KORUPSI DI INSPEKTORAT KABUPATEN SLEMAN - Fadila Agvina; Rumsari Hadi Sumarto (SOCIAL : Jurnal Inovasi Pendidikan IPS, 2026)
ABSTRACT The development of the Integrity Zone constitutes one of the Indonesian government's strategic policies to strengthen bureaucratic reform by promoting integrity, accountability, high-quality public services, and corruption prevention. This policy has become increasingly important because corruption remains a persistent challenge that undermines public governance and weakens citizens' trust in government institutions. This study aims to analyze the implementation of the Integrity Zone policy from the governing perspective at the Inspectorate of Sleman Regency as the Internal Government Supervisory Apparatus (APIP). A descriptive qualitative approach was employed, with data collected through in-depth interviews, observation, and documentation involving three purposively selected key informants. The data were analyzed using the interactive model of Miles, Huberman and Saldaña encompassing data condensation, data display, and conclusion drawing. The findings reveal that the implementation of the Integrity Zone policy is supported by effective communication, organizational resource readiness, strong commitment among implementers, and a well-defined bureaucratic structure coordinated by the Internal Assessment Team (TPI). From the governing perspective, the Sleman Regency Inspectorate performs not only supervisory functions but also facilitative, advisory, and evaluative roles in coordinating policy implementation across government agencies. The study concludes that the synergy between regulatory (regeren), managerial (besturen), and supervisory functions is a critical factor in reinforcing transparent, accountable, and integrity-based governance while strengthening corruption prevention efforts within local government. ABSTRAK Pembangunan Zona Integritas merupakan kebijakan strategis pemerintah untuk memperkuat reformasi birokrasi melalui peningkatan integritas, akuntabilitas, kualitas pelayanan publik, dan pencegahan korupsi. Implementasi kebijakan tersebut memerlukan tata kelola yang efektif agar mampu mendorong perubahan budaya organisasi secara berkelanjutan. Penelitian ini bertujuan menganalisis implementasi kebijakan pembangunan Zona Integritas dalam perspektif governing di Inspektorat Kabupaten Sleman sebagai Aparat Pengawasan Internal Pemerintah (APIP). Penelitian menggunakan pendekatan kualitatif deskriptif dengan pengumpulan data melalui wawancara mendalam, observasi, dan dokumentasi terhadap tiga informan yang dipilih secara purposive. Analisis data dilakukan menggunakan model interaktif Miles, Huberman dan Saldaña yang meliputi kondensasi data, penyajian data, serta penarikan kesimpulan. Hasil penelitian menunjukkan bahwa implementasi pembangunan Zona Integritas didukung oleh komunikasi yang intensif, ketersediaan sumber daya yang memadai, komitmen aparatur yang tinggi, dan struktur birokrasi yang jelas sebagaimana dijelaskan dalam model implementasi kebijakan Edward III. Dari perspektif governing, Inspektorat Kabupaten Sleman tidak hanya menjalankan fungsi pengawasan, tetapi juga berperan sebagai fasilitator, pembina, dan evaluator dalam mengoordinasikan pembangunan Zona Integritas pada perangkat daerah. Penelitian ini menegaskan bahwa sinergi fungsi regeren, besturen, dan pengawasan memperkuat tata kelola pemerintahan yang transparan, akuntabel, berintegritas, serta mendukung upaya pencegahan korupsi di pemerintah daerah.